Analisis Kesalahan Siswa Berdasarkan Kriteria Watson dalam Menyelesaikan Soal Literasi Matematika Persamaan Linear Dua Variabel - Intan Utami; Abdul Basir, Mochamad; Risqi Maharani, Hevy (Cartesian: Jurnal Pendidikan Matematika, 2025)
Errors are a reflection of how students reason and illustration of the process of students’ building their own knowledge. The purpose of this study is to describe the types of errors in solving mathematics literacy problems on topic the system of linear equations of two variables based on Watson's criteria and the factors that cause students to make mistakes. The research subjects consisted of 6 students with high, middle, and low mathematical ability. This research used qualitative approach with data collection techniques were carried out by written tests and interviews. In general, the error made by students is indirect manipulation, namely by moving the coefficient value of a certain variable to another part to obtain the value of the variable being sought. Upper category students made indirect manipulation errors and response level conflicts. Medium category students made missing data errors, indirect manipulation and skill hierarchy problems. Lower group students made errors of improper procedure, missing data, indirect manipulation, skill hierarchy problem, missing conclusion and other than the seven categories. Factors causing errors made by students include, experiencing object-process error misconceptions, deliberate and hasty factors, lack of focus and thoroughness and lack of understanding of number operations, not thinking of writing steps and not knowing the next step to solve it, forgetting and not solving the problem so that he does not write conclusions, difficulty in understanding the problem.